Publisher Correction: Genomes of 13 domesticated and wild rice relatives highlight genetic conservation, turnover and innovation across the genus Oryza. (November 2018) - Stein, Joshua; Yu, Yeisoo; Copetti, Dario; Zwickl, Derrick; Zhang, Li; Zhang, Chengjun; Chougule, Kapeel; Gao, Dongying; Iwata, Aiko; Goicoechea, Jose; Wei, Sharon; Wang, Jun; et al.
This article was not made open access when initially published online, which was corrected before print publication. In addition, ORCID links were missing for 12 authors and have been added to the HTML and PDF versions of the article.